Unified fatigue life prediction of bolts with different sizes and lengths under various axial loading conditions. (January 2022) - Nam, Juhyun; Kim, Dongwon; Kim, Kyungjae; Choi, Sungwon; Oh, Je Hoon
Highlights: A unified S-N curve for bolts under axial loading was proposed based on experiments and simulation. A total of 133 fatigue tests were conducted under 46 different fatigue conditions. Simulation was conducted to calculate the critical multiaxial stress components. Unified S-N curve predicted high-cycle fatigue life with a mean absolute error of 15 %. Abstract: Bolts tend to show different fatigue behavior with respect to the size or shape of a bolt and the level of preload though it is the same material. This makes it difficult to predict the fatigue life of bolts. In this study, a novel method to construct a unified stress-life (S-N) curve was proposed for the three different bolts with different sizes and lengths subjected to various external axial loading conditions and preloads, ranging from 44 % to 88% of the ultimate tensile stress. A total of 133 experiments for 46 different fatigue conditions were conducted and finite element analysis was also performed to calculate multiaxial stress components at the root of the thread. The fatigue characteristics of the bolts were investigated depending on various loading conditions, and the life prediction performance with fitted S-N curves was compared with respect to four mean stress correction models. The unified S-N curve showed high accuracy in life prediction; 15 % mean absolute error without exceeding ± 50 % for finite life loading conditions.